Taking Stock of Innocence: Movements, Mountains, and Wrongful Convictions - Acker, James R. (Journal of contemporary criminal justice, 2017)
This article offers a brief overview of the current state of the Innocence Movement. It begins by reviewing what we know, and do not know, about the incidence of wrongful convictions and their correlates and causes. It then explores select issues that should receive greater attention to help sustain the Innocence Movement and ensure its advancement. Acknowledging that much has been learned about wrongful convictions and that important reforms have been enacted, the article concludes by observing that significant challenges remain and must be addressed before efforts to guard against convicting the innocent are relaxed.